Visual Research in Graphic Novel Form. Issue 2 (3rd April 2022) - Smith, Conrad
Abstract : The first published image in a government report based on a sketch made within the Rocky Mountains appeared in 1843. This report is a visual description of how the author located the viewpoint for that 1842 field sketch with a horizontal error of less than three feet and a vertical error of less than four inches.